EXTRACTION AND CHARACTERIZATION OF FREE NONPOLAR LIPID FRACTION OF CHOCOLATE USING A RAPID ANALYTICAL PROCEDURE - Daniele Naviglio; Lydia Ferrara; Monica Gallo (European Scientific Journal, ESJ, 2014)
In this work has been developed a new analytical procedure to extract the non-polar component of the lipid fraction of the chocolate, in a simple, rapid and economical way and its subsequent analysis by using a gas chromatograph equipped with flame ionization detector (GC-FID). The interest to isolate the non-polar lipid fraction containing triglycerides, waxes, sterol esters and minor components, such as sterols and liposoluble vitamins from the polar fraction could be of three types: analytical, nutritional and commercial. In analytical scope, the quality parameters of the lipid component of chocolate concern the non-polar component. Moreover, the chemical-physical parameters such as the melting point, refractive index, color, etc. were relative to a mixture of fatty substances was not well defined. From the nutritional point of view, the non-polar lipid fraction is the one that gives the largest contribution to the calorific value of the chocolate and then the separation of the two fractions could be useful to better assess the total caloric intake. For economic reasons, not the least important was considering the possibility of fraudulent additions of polar lipid components to replace the non-polar component more valuable, this alteration was not detectable only by applying the official method. The results obtained by the proposed procedure, combined with those obtained with the official method allowed to obtain more complete information on the composition of the lipid component of chocolate. Consequently, the ultimate goal could be reported this information on the nutrition labels of chocolate, for greater product transparency and greater consumer protection.